2018
DOI: 10.4491/eer.2018.322
|View full text |Cite
|
Sign up to set email alerts
|

A new nano-ZnO/perlite as an efficient catalyst for catalytic ozonation of azo dye

Abstract: In this investigation, nano ZnO was sonochemically synthesized by a novel method using a methionine precursor. A narrow size distribution (41-50 nm) of nano ZnO was achieved that was immobilized on perlite and applied as a catalyst in catalytic ozonation. The catalyst was characterized by fourier transform infrared spectroscopy, BET surface area, and field emission scanning electron microscope. The ozonation of recalcitrant Remazol black 5 (RB5) di-azo dye solution by means of the synthesized catalyst was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“… 47 Another study mentioned using a manganese catalyst in heterogeneous catalytic ozonation, indicating that hydroxyl radicals play a significant role in the oxidation process. 48 Shokrollahzadeh et al 17 also reported that adding a nano-ZnO/perlite nanocatalyst increased the degradation rate during the catalytic ozonation of an azo dye. Overall, these references demonstrated that nanocatalysts improved the performance of catalytic ozonation systems by producing hydroxyl radicals.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“… 47 Another study mentioned using a manganese catalyst in heterogeneous catalytic ozonation, indicating that hydroxyl radicals play a significant role in the oxidation process. 48 Shokrollahzadeh et al 17 also reported that adding a nano-ZnO/perlite nanocatalyst increased the degradation rate during the catalytic ozonation of an azo dye. Overall, these references demonstrated that nanocatalysts improved the performance of catalytic ozonation systems by producing hydroxyl radicals.…”
Section: Resultsmentioning
confidence: 98%
“…In the context of Shokrollahzadeh et al (2019) 17 research concerning nano-ZnO/pearl stone use for reactive blue 5 degradation, a higher efficacy was demonstrated, surpassing the 92% TOC removal efficiency. Compared to Zhang et al (2022), 68 who focused on methyl orange degradation by utilizing nano MnO 2 particles, the current study showed slightly lower degradation efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its floatability, rich silica and alumina content, chemically inert nature, perlite has been gaining research interest as a catalyst or catalyst support material these days. Recently, perlite has been reported as a heterogeneous catalyst in numerous applications including, Fenton degradation, [ 10 ] green synthesis of aryl/alkyl methanes, [ 11 ] photocatalysis, [ 12 ] economical preparation of xanthenes, [ 13 ] biodiesel synthesis, [ 14 ] Knoevenagel condensation, [ 15,16 ] azo dye ozonation, [ 17 ] hydrogenation, [ 18 ] etc. It is thus assumed, perlite having richer silica and alumina composition can possess a significant amount of stable surface‐active sites after proper treatment and hence can be converted into a potential heterogeneous acid catalyst for different acid‐catalyzed industrially useful organic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the disadvantages in MBR, pretreatment prior to MBR is required. Advanced oxidation process such as photocatalysis [15], electro-oxidation, ozonation [16] and UV/H 2 O 2 provides a better and compromising solution for pretreatment of wastewater. Electro-oxidation (EO) process increases the biodegradability index (BI) by decomposing the complex compounds, thereby increasing the activity of biological treatment prevailing in the MBR to degrade pollutants.…”
Section: Introductionmentioning
confidence: 99%